Quantitative profiling reveals minor changes of T cell receptor repertoire in response to subunit inactivated influenza vaccine - Sycheva, Anastasiia L; Pogorelyy, Mikhail V; Komech, Ekaterina A; Minervina, Anastasia A; Zvyagin, Ivan V; Staroverov, Dmitriy B; Chudakov, Dmitriy M; Lebedev, Yuri B; Mamedov, Ilgar Z (Vaccine, 2018)
Vaccination against influenza is widely used to protect against seasonal flu epidemic although its effectiveness is debated. Here we performed deep quantitative T cell receptor repertoire profiling in peripheral blood of a healthy volunteer in response to trivalent subunit influenza vaccine. We did not observe significant rebuilding of peripheral blood T cell receptors composition in response to vaccination. However, we found several clonotypes in memory T cell fraction that were undetectable before the vaccination and had a maximum concentration at day 45 after vaccine administration. These cells were found in lower concentration in the course of repertoire monitoring for two years period. Our observation suggests a potential for recruitment of only a limited number of new T cells after each seasonal influenza vaccination.
Keywords: Influenza Vaccines; Male; genetická variace; subjednotkové vakcíny; T cell receptor; High-Throughput Nucleotide Sequencing; TCR repertoires; inaktivované vakcíny; mužské pohlaví; klonální evoluce; T-lymfocyty; vakcíny proti chřipce; receptory antigenů T-buněk; Receptors, Antigen, T-Cell; Vaccines, Subunit; lidé; ženské pohlaví; Inactivated influenza vaccine; Humans; Clonal Evolution; vysoce účinné nukleotidové sekvenování; High-throughput sequencing; Influenza, Human; T-Lymphocytes; Genetic Variation; Female; lidé středního věku; chřipka lidská; Middle Aged; Vaccines, Inactivated